SISTEM INFORMASI DESA SIALANG PANJANG KECAMATAN TEMBILAHAN HULU BERBASIS WEB - Rita Disnasari; Muh. Rasyid Ridha (JURNAL PERANGKAT LUNAK, 2022)
Until now, the Sialang Panjang Village Office does not yet have a special system to assist office staff in providing services to the community. However, there are several reasons why the Sialang Panjang Village Office wants a village system. These reasons include: they do not have a special program that is integrated into the database in terms of community population administration, besides the need for information for the local village community and the wider community is very large, many village communities do not know about village potential, village statistics, and the latest information. village. To overcome this, we need a software development process in the form of a Sialang Panjang Village Information System. The processes carried out are requirements analysis, system design, system implementation, system testing and system maintenance. The development method used is the waterfall method, while the analytical method used is the pieces method which can be a reference in building an information system for the village of Silang Panjang. UML (Unified Modeling Language) as a system modeling language, PHP (Hypertext Preprocessor) as a programming language and MySQL database. Then for system testing using black-box testing, white-box testing and questionnaires. With this village information system, it will be able to assist village office staff in providing services to the community and make it easier for the community to take care of population administration and obtain information. Keywords: Web-Based Information System, Village Service, Sialang Panjang Village